2007
DOI: 10.1099/jmm.0.46762-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative performance of the Roche COBAS Amplicor assay and an in-house real-time PCR assay for diagnosis of Chlamydia trachomatis infection

Abstract: This study investigated the comparative performance of the Amplicor assay and an in-house semi-automated, multiplex real-time PCR for the diagnosis of genital chlamydial infection. Four different assays, the COBAS Amplicor CT test (Amplicor PCR), in-house real-time PCR (IHRT-PCR), in-house nested cryptic plasmid PCR and in-house nested major outer membrane protein PCR, were performed on genital swabs from 1000 consecutive patients attending a genitourinary medicine clinic. The samples were designated true posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Performance of the COBAS Amplicor regarding C trachomatis detection in this study was comparable with its performance in other studies 10 11. In these other studies, similar high sensitivities, specificities, PPVs and NPVs were achieved, as we found in this study.…”
Section: Discussionsupporting
confidence: 90%
“…Performance of the COBAS Amplicor regarding C trachomatis detection in this study was comparable with its performance in other studies 10 11. In these other studies, similar high sensitivities, specificities, PPVs and NPVs were achieved, as we found in this study.…”
Section: Discussionsupporting
confidence: 90%
“…13 The use of the BD ProbeTec in the 2008 study could possibly have biased the observed differences between 2005 and 2008. However, since Amplicor is generally less specific and more sensitive for both NG and CT than ProbeTec, [44][45][46][47] although some studies found them as quite equivalent, 42,48 the upward trend in NG from 2005 to 2008 could be more pronounced than observed, which would not affect our conclusions.…”
Section: Discussionmentioning
confidence: 62%
“…This study has validated the C trachomatis assay previously described by Jalal et al ,7 for use with first-void urine specimens.…”
Section: Discussionmentioning
confidence: 69%